Preparation of polymer electrolyte membrane for lithium batteries by radiation-induced graft copolymerization - Nasef, Mohamed Mahmoud; Sopiah, Raja Rajeswati; Mohd. Dahlan, Khairul Zaman (2004)
A polymer electrolyte membrane for lithium batteries was prepared by radiation- induced graft copolymerization of styrene monomer onto poly(vinylidene fluoride) (PVDF) film and subsequent chemical activation with liquid electrolyte consisting of lithium hexafluorophosphate (LiPF6) in a mixture of diethylene carbonate/ethylene carbonate (DC/DEC) of known composition. The chemical changes in the PVDF films after styrene grafting and subsequent chemical activation were monitored by FTIR spectroscopic analysis. The swelling in electrolyte solution (electrolyte uptake) and the ionic conductivity of the membranes were determined at various degrees of grafting. The conductivity of the membranes was found to be a function of the degree of grafting and reached a magnitude of 10(-3) S/cm at a degree of grafting of 50 %. The results of this work suggest that radiation-induced graft polymerization provides an alternative method to substitute blending in preparation of polymer electrolyte membranes for application in lithium batteries.